Locomotor control patterns during the pole vault approach phase - Needham, L.; Bezodis, I.; Exell, T.; Simpson, S.; Irwin, G. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The aim of this study was to investigate the visual regulation of locomotion during the pole vault approach phase on athletes of differing skill levels. Seven well-trained athletes performed six jumps which were recorded and analysed. Pole vaulters utilised three locomotor control patterns. However, these were not associated with skill level. The non-stable nature of footfall Variability in athletes enforces the need for degeneracy in approach phase movement patterns. Coaches should include training exercises that require intentional use of visual regulation to aid athletes in achieving the flexibility to adapt to changing constraints during the approach phase. Athletes should be considered on an individual basis in order to effectively, efficiently and safely improve performance. Practical solutions are offered which provide examples of how individual locomotor patterns can be interpreted to inform the prescription of training interventions.